Compare the Outcomes of Orchidopexy with and without SAC Ligation in Children with Palpable Testicals: A Retrospective/Cross-Sectional Study - Syed Azhar Hussain, Zakir Hussain Rajpar, Kashifuddin Qayoom Soomro, Shoukat Ali Mughal, Afhan Qayoom Shaikh, Aijaz Shaikh, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare the outcomes of orchidopexy with and without sac ligation in term of operative time and development of inguinal hernia in children presented with palpable testis. Study design: Retrospective/cross-sectional Duration and place of study: Department of Urology, Liaquat University of Medical and Health Sciences, Jamshoro during from the period June 2022 to July 2023. Methodology: Eighty patients were chosen for this investigation and divided into two equal groups 40 patients in each group. Group A comprised cases where orchidopexy was executed without dissection and ligation of the peritoneal sac, whereas Group B encompassed patients in whom sac ligation was conducted. The average surgical duration was documented for each instance. Post-operative follow-ups were conducted at one, four, eight, and twelve weeks. Patients were assessed for post-operative hernia during each follow-up, and the findings were documented. Results: The mean age of patients in Group A was 5.62±2.04 years, whereas in Group B it was 5.43±1.88 years. The study results indicated that 50 (62.5%) individuals exhibited left unilateral cryptorchidism, whereas 30 (37.5%) patients presented with right unilateral cryptorchidism. The average surgical time for patients in the no sac ligation group was 24.32±2.83 minutes, whereas in the ligation group it was 37.46±3.24 minutes. Statistically, the two groups exhibited a very significant difference with a p-value of 0.001. No post-operative hernias were seen in any patients from either group. Conclusion: Based on the findings of our research, we came to the conclusion that orchidopexy without sac ligation requires less time during the operation and does not pose any danger of post-operative hernia. Keywords: Orchidopexy, Palpable Testicles, Sac Ligation, Operative Time, Inguinal Hernia